PENGARUH PENERAPAN MODEL PEMBELAJARAN INVESTIGASI KELOMPOK TERHADAP HASIL BELAJAR MATEMATIKA - Ireneus Rendi Sukardi; Gregorius Taga; Ariswan Usman Aje (JUPIKA: JURNAL PENDIDIKAN MATEMATIKA, 2024)
This research aims to (1) produce Group Investigation learning tools on line pattern material for Class VIII students of SMP Negeri 1 Ende. (2) to determine learning outcomes through the Group Investigation Learning Model on line pattern material for Class VIII students of SMP Negeri 1 Ende. The type of research used is Experimental Research Type. The population in the study were VIII grade students totalling 160 people. The sample was class C as a control class totaling 29 people and class A as an experimental class totaling 29 people. The research instrument used is a test instrument. Based on the results of the study, the post-test data in the control class and the experimental class were normally distributed and homogeneous, so the hypothesis testing in this study used the t-test. The data on students' mathematics learning outcomes obtained a value of s 2.189, while in the table of t distribution values with a significance level  The results of the t-test calculation show that the value of s is greater than the value of or (2.189>2.003). Based on the decision can be concluded that s rejected and 1 is accepted. This means that there is an effect of the group investigation learning model on the mathematics learning outcomes of class VIII students' row pattern material at SMP Negeri 1 Ende.